Data analysis in the care of Elaeis guineensis (african palm) in Colombia, Ecuador and Peru - Jaimes Becerra, Jesus Ramon (2023)
This article analyzes in a comparative way how the availability or not of data on plantations, through updated national records, can affect the increase or decrease in the production of palm oil, a derivative of Elaeis guineensis. For which a correlational analysis is carried out between the variations presented in the production of palm oil in Ecuador, Colombia and Peru, during the last 20 years, to discover if there are connections or not, in order to determine if the neighboring countries are They are affected by bud rot and other oil palm pests in the same way as Ecuador. The Excel programs in their most recent version 2020 and Eviews 6.0 are used in order to make the connection and the regressive connection of the palm oil production of these three countries, finding that despite the geographical proximity in their plantations there is no between the growth rate of the countries. Which leads to the conclusion that it would be convenient to implement modern data analysis system, starting with a national registry for palm producers in Ecuador, since the falls in palm production have always been greater than in Colombia and Peru, which it does have a registration system or national plan for its development.